State Financial Position as State Equity Participation in Indonesia Investment Authority - Al Farizy, Mohammad Rafi; Nugroho, Fiska Maulidian; Prakoso, Bhim (Universitas Semarang, 2024)
The aim of this research is to examine the position of state finances as state capital participation in the INA. Through Government Regulation in Lieu of Law (PERPPU) No. 2/2022, the Investment Management Institution as known as Indonesia Investment Authority (INA) is a new initiative by the government to manage Central Government investments. Referring to the Santiago Principles, the government uses the separate legal entity model for the establishment of INA. The capital of INA comes from state equity participation, which in Indonesia’s financial system is categorized as separate state assets. This means that, in essence, INA’s capital is considered state finance. However, there is a regulatory construction in Article 158 paragraph (4) which states that INA’s losses are not state losses, thus INA’s equity is no longer considered state finance. This is akin to the concept of a separate legal entity in corporations, which have their own assets separate from the assets of their owners/managers. Previously, Constitutional Court Decisions No. 48/PUU-XI/2013 and No. 62/PUU-XI/2013 had established that separated state assets remain state finance. Therefore, a question arises regarding the status of INA. Using normative legal research methods, the research findings indicate that INA’s equity originating from state equity participation has transformed into INA’s private finance. However, this transformation is not in line with the national financial system constructed based on the welfare state principle. Consequently, this could potentially create loopholes for the embezzlement of state funds.